Using species distribution modelling to identify 'coldspots' for conservation of freshwater fishes under a changing climate. Issue 4 (27th February 2022) - Stewart, Barbara A.; Ford, Benjamin M.; Benson, Justin A.
Abstract: Like other Mediterranean regions, south‐western Australia is predicted to experience an increase in temperature and drought conditions as a result of climate change, leading to altered species distributions. This study provides the first assessment of the effectiveness of the reserve system in Australia for conserving native freshwater fish by considering the congruence between protected areas and potential climate refugia in a global biodiversity hotspot. Using species distribution modelling, exposure to climate change was predicted for 13 native fish taxa, and priority areas (refugia) for fish conservation were identified by overlapping the present and future suitable climate envelopes of these taxa. Areas with climate refugia for >70% of the native freshwater fish fauna were recognized as 'coldspots'. Two taxa were predicted to lose all suitable climate in the region by 2080, and five other taxa were predicted to lose >80% of their area of suitable climate. A 'coldspot' was identified consisting of a core area where >80% of taxa were predicted to persist and a larger surrounding area where >70% of taxa were predicted to persist. Although 93% of the core area of the coldspot is at present contained within the established protected areas network, only 26% of the surrounding area is contained within reserve boundaries. Future conservation actions, including the design and implementation of the protected area network, should take this coldspot into consideration.